Influence of Hydroxyethyl Cellulose and Glycerin Concentration Variations on the Physicochemical Stability of Niacinamide- Loaded Nanoparticle Serum Formulations - Risa Ahdyani,; Patimah, Raudatul; Fatmasari, Erlina; Rahayu, Sri; Annisa, Rifka (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: Niacinamide is widely used in cosmeceutical formulations for anti-aging and hyperpigmentation treatment. However, its instability and limited penetration through the stratum corneum reduce its efficacy. Nanoparticle-based facial serum systems incorporating hydroxyethyl cellulose and glycerin have the potential to improve niacinamide stability, control its release, and enhance skin penetration. Objective: This study aimed to evaluate the effect of hydroxyethyl cellulose and glycerin concentrations on the physicochemical stability of niacinamide-loaded nanoparticle serum using a factorial design. Method: Niacinamide nanoparticle serum was formulated by ionic gelation and optimized using a 2² factorial design, yielding four formulations. Nanoparticles were prepared using chitosan and sodium alginate and incorporated into serum containing hydroxyethyl cellulose and glycerin, followed by evaluation of particle characteristics, physicochemical properties, and stability using cycling tests with pre- and post-test comparisons analyzed by a paired sample t-test. Results: All formulations produced nanoparticles within the nanometer range (134.7–152.2 nm) with acceptable size distribution (PDI 0.610–0.926) and zeta potential around −30 mV, and exhibited satisfactory physicochemical properties, including adhesion (>4 s), spreadability (5–7 cm), viscosity (273.33–1208.33 cP), and pH (4.72–5.55). Conclusion: All formulas meet the ideal characterization, and there is no significant difference between the before and after stability testing for the niacinamide nanoparticle serum, except viscosity result.